Hormonal Response of Gibberellin (Ga3), Grafting and Seasonal Variations on Growth and Yield Parameters on Okra (Abelmoschus Esculentus) (American International Journal of Biology and Life Sciences, 2019)
The effect of Gibberellin Hormonal Response and Grafting methods on the Growth and Yield of Okra was investigated, with the aim of inducing variability that could be exploited in the improvement of some quality traits in Okra plants. Gibberellin, grafting and a combination of grafting with Gibberellin) were applied on to the Okra seeds. The seeds of Okra were treated at four different concentrations of Gibberellin (0.1mM, 1.0 mM, 2.0 mM and 0.0 mM as control) after which some of the mutants were grafted using tongue grafting method at seedlings stage.  The other set of seeds were not treated with the hormone but were grafted at seedlings stage. The results obtained revealed highly significant difference (P≤ 0.01) in the effects of Gibberellin on survival rates, number of fruits, and fruit weight. Similarly, highly significant differences (P≤0.01) were found between the treatments in Survival rate, except on the number of fruits and fruit weight, where no significant differences exist. More so, significant differences were found in the traits between the seasons except in fruit number. The result showed that Gibberellin and grafting improve important quality traits of Okra. The mutants and grafted Okra could be grown both during the rainy and dry seasons, while 0.1 mM concentration of Gibberellin and grafting improve some important quality traits of Okra that could be utilized for further improvement of Okra. However, the response of Okra to grafting was higher. Based on the findings, the study concluded that, grafting improves some important quality traits of Okra that are of high economic value and possible recommendations that could be made.